EDUCATIONAL SERVICES AS A STRATEGIC RESOURCE FOR THE SOCIO-ECONOMIC DEVELOPMENT OF THE REPUBLIC OF UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article examines the importance of educational services as a strategic resource for the socio-economic development of the Republic of Uzbekistan. It reveals the economic essence of educational services, their role in the formation of human capital, the improvement of labor force quality, and the development of the country’s innovative potential. Special attention is paid to current trends in the development of the education sector in Uzbekistan, including the expansion of higher education, the growth in the volume of educational services, and their increasing importance in the structure of the national economy. The article emphasizes that the effectiveness of educational services depends not only on quantitative indicators, but also on the quality of education, the professionalism of teachers, students’ motivation, and the correspondence of educational programs to labor market requirements. It is concluded that the further development of educational services is an important condition for sustainable economic growth, social stability, and strengthening the competitiveness of the Republic of Uzbekistan.
Keywords: educational services, human capital, socio-economic development, Republic of Uzbekistan, knowledge economy, higher education, labor market, innovative development, quality of education, strategic resource.